1997
DOI: 10.2135/cropsci1997.0011183x003700020038x
|View full text |Cite
|
Sign up to set email alerts
|

A High‐Density Soybean Genetic Map Based on AFLP Markers

Abstract: Genetic marker systems have improved dramatically in the past 10 yr. Each new system needs to be evaluated for its distribution of markers on genetic linkage maps to validate its use for genetic analysis. The resulting maps are also useful for establishing the genetic positions of genes affecting important phenotypes. We have constructed a high density map in soybean [Glycine max (L.) Merr.] using a 300 RIL (recombinant inbred line) population from BSR‐101 × PI437.654 by first constructing an RFLP (restriction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
101
3
4

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(111 citation statements)
references
References 0 publications
3
101
3
4
Order By: Relevance
“…In spite of its polyploid origin, the soybean composite genetic map is well developed. The classical map contains only 67 loci on 19 linkage groups (Hedges and Palmer, 1993) (Mansur et al, 1996); a University of Nebraska population derived from Clark 3 Harosoy (Shoemaker and Specht, 1995); a USDA/ Iowa State University population, an F2-derived mapping population from A81-356022 (G. max) 3 PI468.916 (G. soja), with 59 F2 plant derivatives (Shoemaker and Olson, 1993;Shoemaker and Specht, 1995;Keim et al, 1996) Marek and Shoemaker, 1997;Danesh et al, 1998;Tomkins et al, 1999;Meksem et al, 2000 The soybean genome comprises about 1.1 Mb/Cvalue (Arumuganathan and Earle, 1991). This makes it about seven and one-half times larger than the genome of Arabidopsis but less than one-half the size of the maize genome (Arumuganathan and Earle, 1991).…”
Section: Current Status Of Soybean Genomicsmentioning
confidence: 99%
“…In spite of its polyploid origin, the soybean composite genetic map is well developed. The classical map contains only 67 loci on 19 linkage groups (Hedges and Palmer, 1993) (Mansur et al, 1996); a University of Nebraska population derived from Clark 3 Harosoy (Shoemaker and Specht, 1995); a USDA/ Iowa State University population, an F2-derived mapping population from A81-356022 (G. max) 3 PI468.916 (G. soja), with 59 F2 plant derivatives (Shoemaker and Olson, 1993;Shoemaker and Specht, 1995;Keim et al, 1996) Marek and Shoemaker, 1997;Danesh et al, 1998;Tomkins et al, 1999;Meksem et al, 2000 The soybean genome comprises about 1.1 Mb/Cvalue (Arumuganathan and Earle, 1991). This makes it about seven and one-half times larger than the genome of Arabidopsis but less than one-half the size of the maize genome (Arumuganathan and Earle, 1991).…”
Section: Current Status Of Soybean Genomicsmentioning
confidence: 99%
“…To date, random amplified polymorphic DNA (RAPD), restriction fragment length polymorphisms (RFLP), amplified fragment length polymorphism (AFLP), simple sequence repeat (SSR), and single nucleotide polymorphism (SNP) markers have been used to construct genetic linkage maps and a consensus map in soybean using many different mapping populations (Shoemaker et al, 1995;Lark et al, 1995;Keim et al, 1997;Song et al, 2004;Cregan et al, 1999;Song et al, 2004;Kassem et al, 2006Kassem et al, , 2012Choi et al, 2007;Hyten et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…AFLP has been used to examine the genetic relationships among other crop species. These include potato (van Eck et al, 1995), lettuce (Hill et al, 1996), rice (Cho et al, 1996), barley (Powell et al, 1997), soybean (Keim et al, 1997), maize (Vuylsteke et al, 1999), eggplant (Mace et al, 1999), and sunflower (Quagliaro et al, 2001). Previous studies showed that an AFLP analysis has greater discriminatory power than a RAPD analysis and other genomic fingerprinting methods.…”
Section: Introductionmentioning
confidence: 99%